Pengalaman Usaha, Inovasi, Keunggulan Kompetitif Dan Pertumbuhan Penjualan Berdampak Pada Kinerja Keuangan UMKM - As’ari, Hasim; Wafa, Zaenal; Airawaty, Diana (Universitas Nusantara PGRI Kediri, 2024)
This study aimed to determine the effect of business experience, innovation, and competitive advantage on sales growth and the impact of sales growth on the financial performance of MSMEs (Micro, Small, and Medium Enterprises). This type of research is quantitative. The research was conducted in Yogyakarta. The study subjects were MSME business owners, with a total sample of 100 respondents using convenience sampling/incidental sampling techniques. Hypothesis testing using SPSS. Testing of research data using validity tests, reliability tests, classical assumption tests, and t-tests. The results of the study showed that business experience, innovation, and competitive advantage affected sales growth, and sales growth also impacted the financial performance of MSMEs. The results of this finding are very relevant for MSME actors because business is no longer like it used to be, so MSME actors continue to innovate to increase competitive advantages, which are important factors in sales growth. In addition, sales growth is a factor that influences the financial performance of MSMEs